2022
DOI: 10.1088/2516-1091/ac93d3
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline based polymers in tissue engineering applications: a review

Abstract: A number of conducting polymers (CPs), such as polyaniline (PANi), as well as functionalized aniline copolymers and composites, which are simultaneously biodegradable and conductive, have been conceptualized as electrically conductive polymer based scaffolds for tissue engineering (TE) in recent years. The rationale behind these scaffolds is to induce “electroactivity” in scaffolds, as many research works have shown that an intrinsic electrical activity leads to both increased rates and improved healing of dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 162 publications
0
19
0
Order By: Relevance
“…This tremendous breakthrough has led to commercial applications of the Na 2 O-CaO-P 2 O 5 -SiO 2 system for bone repair, enamel-healing toothpaste, dental restoration, drug delivery, and so forth [ 22 , 23 , 24 ]. Then, the interests of scientists evolved toward polymeric materials, ceramics, and composites [ 25 , 26 , 27 , 28 ]. Currently, most attention is paid to mixed materials, often referred to as hybrid materials, mainly based on combinations of bioglasses and ceramics with appropriately modified polymer matrices [ 29 , 30 ] or hybrids in which a covalent bond connects individual components; for instance, polyhedral oligomeric silsesquioxanes (POSSs) and double-decker silsesquioxanes (DDSQs), in which the inorganic silsesquioxane core is bonded with organic side arms [ 7 , 20 , 31 , 32 ].…”
Section: Selected Biomaterials Based On Cage-like Silsesquioxanesmentioning
confidence: 99%
“…This tremendous breakthrough has led to commercial applications of the Na 2 O-CaO-P 2 O 5 -SiO 2 system for bone repair, enamel-healing toothpaste, dental restoration, drug delivery, and so forth [ 22 , 23 , 24 ]. Then, the interests of scientists evolved toward polymeric materials, ceramics, and composites [ 25 , 26 , 27 , 28 ]. Currently, most attention is paid to mixed materials, often referred to as hybrid materials, mainly based on combinations of bioglasses and ceramics with appropriately modified polymer matrices [ 29 , 30 ] or hybrids in which a covalent bond connects individual components; for instance, polyhedral oligomeric silsesquioxanes (POSSs) and double-decker silsesquioxanes (DDSQs), in which the inorganic silsesquioxane core is bonded with organic side arms [ 7 , 20 , 31 , 32 ].…”
Section: Selected Biomaterials Based On Cage-like Silsesquioxanesmentioning
confidence: 99%
“…Additionally, copolymerization of altered biodegradable and electroactive macromers or block copolymers is another approach that could be utilized to achieve the biodegradability of conductive polymers while maintaining or enhancing electroconductivity. These methods enable the combination of advantageous features of both conductive polymers and biodegradable polymers. …”
Section: Degradability and Cytotoxicity Effect Of Conductive Hydrogelsmentioning
confidence: 99%
“…In vitro studies testing the hydrogel's cytocompatibility by culturing cells on the degraded products showed that the AT-containing hydrogel reduced inflammation compared to the AT-free hydrogel. However, in vivo studies on the biocompatibility of PANi have yielded conflicting results . Wang et al observed inflammation and encapsulation of implanted PANi in the Sprague-Dawley rat model, while Mattioli-Belmonte et al showed no significant inflammatory reaction after 4 weeks of implantation in the same rat model.…”
Section: Degradability and Cytotoxicity Effect Of Conductive Hydrogelsmentioning
confidence: 99%
“…16 In this context, the application of conductive materials with the capability to track cellular behavior in a three-dimensional environment is one of the most fascinating areas of future research. Thus far, several conductive materials have been recognized, i.e., polypyrrole (PPy), 17 polyaniline (PANI), 18 and poly (3,4-ethylenedioxythiophene) (PEDOT). 19,20 However, carbon-based materials, such as graphite, 21 ake graphene, graphene oxide, carbon nanobers, and carbon multiwalled nanotubes, offer considerable prospects and are subjected to intensive evaluation for such applications.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, several conductive materials have been recognized, i.e. , polypyrrole (PPy), 17 polyaniline (PANI), 18 and poly(3,4-ethylenedioxythiophene) (PEDOT). 19,20 However, carbon-based materials, such as graphite, 21 flake graphene, graphene oxide, carbon nanofibers, and carbon multiwalled nanotubes, offer considerable prospects and are subjected to intensive evaluation for such applications.…”
Section: Introductionmentioning
confidence: 99%